(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s
(3ChdgG (B:s
(3GdNGA hGdLje hGdfhf , fNL GdSjd ai SfO GdhGOi jfNL fNLG UOeg hfNL GdQLd GdeQCI jfNLgG fNLG fci s
(3BNQgG (B:s
(3ef GdNGA hGdSjf hGdhGh , bhdg (B: (3hGdUhGH GdCQVhf ebdhHg (B: (3SGNJ Hge GdCQV GfNSaJ hai GdecGf ShGNjI hUGQJ GdCQV ShGNkG s
(3HgG fXGe GdJYbjHIs
(3HgG WeSs
(3fSNI YGTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B212 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs